MAP Kinase FgHog1 and Importin β FgNmd5 Regulate Calcium Homeostasis in Fusarium graminearum - Lixin Zhang; Yiqing Li; Lanlan Dong; Kewei Sun; Hao Liu; Zhonghua Ma; Leiyan Yan; Yanni Yin (Journal of Fungi, 2023)
Maintaining cellular calcium (Ca2+) homeostasis is essential for many aspects of cellular life. The high-osmolarity glycerol (HOG) mitogen-activated protein kinase (MAPK) pathway responsible for signal integration and transduction plays crucial roles in environmental adaptation, especially in the response to osmotic stress. Hog1 is activated by transient Ca2+ increase in yeast, but the functions of the HOG pathway in Ca2+ homeostasis are largely unknown. We found that the HOG pathway was involved in the regulation of Ca2+ homeostasis in Fusarium graminearum, a devastating fungal pathogen of cereal crops. The deletion mutants of HOG pathway displayed increased sensitivity to Ca2+ and FK506, and elevated intracellular Ca2+ content. Ca2+ treatment induced the phosphorylation of FgHog1, and the phosphorylated FgHog1 was transported into the nucleus by importin β FgNmd5. Moreover, the increased phosphorylation and nuclear accumulation of FgHog1 upon Ca2+ treatment is independent of the calcineurin pathway that is conserved and downstream of the Ca2+ signal. Taken together, this study reported the novel function of FgHog1 in the regulation of Ca2+ homeostasis in F. graminearum, which advance the understanding of the HOG pathway and the association between the HOG and calcineurin pathways in fungi.